Wine, love or divine love? Analysing three short traditional Algerian Sha'bî Songs. Issue 2 (3rd March 2020) - Touati, Samia
ABSTRACT: Although very popular, Algerian sha'bî music has not received the interest it deserves from academic research yet. This article explores this artistic genre, which draws its inspiration from Andalusian music and malhûn poetic tradition, with regard to the sufi influence that colours some of its typical productions. Through the analysis of three short Algerian sha'bî songs, this article will demonstrate that this artistic world is profoundly impregnated with sufi symbolism, especially while comparing Divine love to wine.